Update in palliative care in gynecologic oncology. Issue 1 (25th October 2021) - Karlin, Daniel; Khoo, Teresa; Pietras, Christopher
Abstract : Purpose of review: This review summarizes research advances in quality of life, symptom management, and end-of-life practices within palliative care that can benefit patients with gynecologic cancers. Recent findings: Addressing fertility issues, sexual side effects, and possible disease recurrence can promote quality of life in gynecologic cancer survivors. Cannabis can provide some benefit for nausea and neuropathic pain, yet for nonneuropathic pain presentations, it does not appear to provide significant benefit in reducing opioid usage. Lastly, palliative care outcomes, such as reduced aggressive care at the end of life and higher rates of hospice enrollment are augmented by the presence of an outpatient palliative care clinic. Summary: Ongoing advances in palliative care research hold potential for improvement in systems delivery of palliative care as well as symptom management and psychosocial support.